Improving Students’ Writing Participation and Achievement in an Edpuzzle-Assisted Flipped Classroom - Luki Emiliya Hidayat; Muhammad Dzulfiqar Praseno (EDUCAFL : Journal of Education of English as Foreign Language, 2021)
Writing is often considered as a dull but challenging skill to be learned. Hence, a learning innovation aside the conventional methods is needed to improve students’ participation and achievement. Flipped Classroom, a reverse teaching strategy was selected to overcome this problem because it involves the use of technology as a learning media that fits the characteristics of millennial students. This strategy was combined with Edpuzzle, a learning media which provides content from renowned education channels that can be customized and used freely by teachers. The combination of Flipped Classroom strategy and Edpuzzle has proven to be successful in improving students’ participation in learning activities (30.5%) as well as their achievement in writing (17%). Therefore, teachers are suggested to implement and adapt this practice in their class while considering the competence to be mastered, as well as students’ needs and characteristics.